Analysis of Differentially Expressed Proteins and Modifications Induced by Formaldehyde Using LC-MS/MS - Ranran Liu; Yue Han; Zhiyue Wu; Jianji Zhang; Yong Zang; Lijin Shen; Shanshan Tian; Kai Zhang (Separations, 2022)
Formaldehyde (FA) is a toxic compound that is considered to have a carcinogenic effect due to its damage to biological macromolecules. However, the influence of FA at the protein level remains to be explored. Here, we used LC-MS/MS to identify the differentially expressed proteins and modifications to proteins between FA-treated and untreated HeLa cells. Among 2021 proteins identified, 196 proteins were significantly down-regulated and 152 up-regulated. The differentially expressed proteins were further analyzed using bioinformatics tools for annotating the characterization of their localizations and functions. To evaluate the interaction of FA with proteins, we performed proteomic analysis for a mass shift of 12 Da on the side chains of lysine, cysteine and tryptophan, which are induced by FA as noticeable signals. We identified the modified proteins and sites, suggesting direct interaction between FA and proteins. Motif analysis further showed the characterization of amino acid sequences that react with FA. Cluster analysis of the modified proteins indicated that the FA-interacting networks are mostly enriched in the nuclei, ribosomes and metabolism. Our study presents the influence of FA on proteomes and modifications, offering a new insight into the mechanisms underlying FA-induced biological effects.